PENGARUH CONTENT MARKETING TERHADAP CUSTOMER RETENTION DENGAN CUSTOMER ENGAGEMENT SEBAGAI MEDIATOR PADA PENGGUNAAN SITUS WEB ZOMATO - Nabilla, Zulfa; Rubiyanti, R. Nurafni (Economic Faculty, Attahiriyah Islamic University, 2020)
Purpose- The purpose of this survey was to analyze the influence of content marketing on customer retention and customer engagement as a mediated variable on the use of the Zomato website in Bandung. Design/methodology/approach- The research method uses a descriptive analysis with purposive sampling technique. A total sample of 100 respondents with various consideration of characteristics. The statistical analysis used is SEM PLS. Findings- The result of a research that content marketing variables have a significant effect on customer engagement. Customer engagement variables have a significant effect on customer retention. Content marketing variables have a significant effect on customer retention. The customer engagement variable acts as a full mediator between content marketing and customer retention. Implications- The test results show that good content will improve the quality of a company’s involvement with customers and create customer loyalty to the company. Keywords: Content Marketing, Engagement, Retention